GENDER JUSTICE ANALYSIS ON HUSBAND NUSYUZ - Dian Wahyu Ningsih (Universitas Islam Negeri (UIN) Mataram, 2020)
Islam as a religion that is rahmatan lil 'alamin regulates human life including household life, one of which is the matter of nusyuz both from the wife (surah an-Nisa' (04): 34) and husband (surah an-Nisa '(04): 128). However, in some ways, nusyuz is understood to be gender-biased and socially, there are still many problems with husband's nusyuz in the community, one of which occurs in Taman Sari Village, Gunungsari District, West Lombok Regency. Nusyuz husband here can be defined as domestic violence whether physical, psychological, sexual or household neglect. Therefore the focus in this study is (1) understanding and practice of husband's nusyuz in the community; (2) types and causes of nusyuz in the community; (3) Nusyuz practice with a gender perspective.